2002
DOI: 10.1002/ana.10219
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of age and severity on the risk of dementia in Parkinson's disease

Abstract: Age and severity of extrapyramidal signs have been consistently associated with incident dementia in Parkinson's disease. We evaluated the separate and combined effects of age and severity of extrapyramidal signs on the risk of incident dementia in Parkinson's disease in the setting of a population-based prospective cohort study. Age and the total Unified Parkinson's Disease Rating Scale motor score at baseline evaluation were dichotomized at the median. Four groups of Parkinson's disease patients were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
107
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(122 citation statements)
references
References 53 publications
10
107
2
3
Order By: Relevance
“…3 is increasingly recognized as an associated feature of PD in advanced ages and severe disease phases [27].…”
Section: Dementiamentioning
confidence: 99%
“…3 is increasingly recognized as an associated feature of PD in advanced ages and severe disease phases [27].…”
Section: Dementiamentioning
confidence: 99%
“…On the other hand, the increased age-related dementia risk does not seem to be associated with the possible influence of age of onset of motor symptoms; in other words, patients develop dementia in a similar mean age, regardless of when the motor signs appear 54 . Other studies also showed that cognitive impairment in PD correlates with the severity of motor disabilities, male gender, low education, visual hallucinations and the presence of rigidity and axial bradykinesia 55 .…”
Section: Cognitive Deficitmentioning
confidence: 88%
“…In fact, the presence of cognitive impairment or dementia in PD patients is associated with loss of independence, poor quality of life and shortening of lifespan. Moreover, individuals in advanced stages of PD who develop dementia, often present a functional decline that follows a stereotyped pattern, indicating that the beginning of this sign announces the need for a more intensive care and increased risk of mortality 54 . Thus, the onset and progression of cognitive impairment in PD have an important influence on patient management and prognosis.…”
Section: Cognitive Deficitmentioning
confidence: 99%
“…Population studies have shown a direct relationship between patient age and the prevalence of dementia in patients with PD, which is higher than 60% in individuals over the age of 80 years 2,19,20 .…”
Section: Discussionmentioning
confidence: 99%